The importance of patient engagement in the multimodal treatment of MASLD - Joost Boeckmans; Hannes Hagström; Donna R. Cryer; Jörn M. Schattenberg (Communications Medicine)
Abstract Metabolic dysfunction-associated steatotic liver disease (MASLD) is often regarded in society as a disease caused by personal lifestyle and dietary choices. Healthcare providers who have empathy and are able to explain the disease trajectory can better engage with people with MASLD and actively work with them to improve their metabolic health on a sustainable basis. Non-invasive tests can assist in this process, but healthcare providers must ensure they explain their advantages and limitations. Discussing and setting lifestyle goals are priorities before initiating specific pharmacological treatment, since living a healthy lifestyle will remain the backbone of the multimodal management of MASLD. In this review, we discuss challenges and opportunities to actively engage with people living with MASLD in a multimodal treatment framework as a healthcare provider.